Evaluation of Online Learning Programs at Universities Using the CIPP Model - Eka Damayanti; Misykat Malik Ibrahim; Muh. Ilyas Ismail (Jurnal Educative: Journal of Educational Studies, 2021)
Online learning during the COVID-19 pandemic had both positive and negative effects, including online learning for the Dirasah Islamiyah study program, concentration on Education and Teacher Training, Postgraduate at Islamic State University of Alauddin Makassar, so it is necessary to be evaluated. The purpose of this study is to evaluate online learning programs using the Context, Input, Process, and Product (CIPP) program evaluation model formulated by Stufflebeam. This descriptive quantitative research used primary data collected from questionnaires from lecturers and students in the Learning Program Evaluation course as a source of informants and secondary data were taken using documentation in the form of Semester Learning Plans, lecture materials, and coursework results. The collected data were analyzed using descriptive statistical analysis. The results showed that the implementation of online learning at the Postgraduate Alauddin State Islamic University in Makassar, the Dirasah Islamiyah Study Program with the concentration of Education and Teacher Training had been going well although some parts still needed to be improved such as maximizing the use of the Learning Management System (LMS), clear coordination between fellow lecturers who support courses related to RPS which will be applied for one semester and strict conditioning so that students do their assignments responsibly (free of plagiarism).Pembelajaran daring yang berlangsung selama pandemi covid-19 menimbulkan dampak positif dan juga negative, tidak terkecuali pada pembelajaran daring program studi Dirasah Islamiyah konsentrasi Pendidikan dan Keguruan, Pascasarjana Universitas Islam Negeri Alauddin Makassar sehingga perlunya dilakukan evaluasi terhadap program pembelajaran daring tersebut. Tujuan penelitian ini untuk mengevaluasi program pembelajaran daring dengan menggunakan model evaluasi program Context, Input, Process, and Product (CIPP) yang dirumuskan oleh Stufflebeam. Penelitian kuantitatif deskripstif ini menggunakan data primer yang dikumpulkan dari hasil kusioner dari dosen dan mahasiswa pada mata kuliah Evaluasi Program Pembelajaran sebagai sumber informan dan data sekunder yang diambil menggunakan dokumentasi berupa Rencana Pembelajaran Semester, materi perkuliahan, dan hasil tugas mata kuliah. Data yang terkumpul dianalisis menggunakan analisis statistik deskriptif. Hasil penelitian ini Â menunjukkan bahwa pelaksanaan pembelajaran daring di Pascasarjana Universitas Islam Negeri Alauddin Makassar, Program Studi Dirasah Islamiyah konsentrasi Pendidikan dan Keguruan mata kuliah Evaluasi Program Pembelajaran sudah berjalan dengan baik meskipun ada beberapa bagian yang masih perlu ditingkatkan seperti memaksimalkan penggunaan Learning Management Sistem (LMS), koordinasi yang jelas antara sesama dosen pengampu mata kuliah terkait Rencana Pembelajaran Semester (RPS) yang akan diterapkan selama satu semester dan pengkondisian yang ketat agar mahasiswa mengerjakan tugasnya secara bertanggungjawab (bebas plagiasi).